Capacitive Sensors: Ultra‐Facile Fabrication of Stretchable and Transparent Capacitive Sensor Employing Photo‐Assisted Patterning of Silver Nanowire Networks (Adv. Mater. Technol. 6/2016). Issue 6 (September 2016) - Jun, Sungwoo; Ju, Byeong‐Kwon; Kim, Jong‐Woong
Abstract : In article number 1600062, Sungwoo Jun, Byeong‐Kwon Ju, and Jong‐Woong Kim present a method to make fine patterns of silver nanowires on an elastomeric polymer by a fast and chemical‐free approach. This simple method enables stretchable and transparent conducting patterns to be fabricated, which is demonstrated by showcasing a reliable stretchable capacitive sensor.